THE EFFECT OF SMM, ONLINE CUSTOMER REVIEW, AND RATING ON PURCHASING DECISIONS FOR DAPOER INTAN ON MARKETPLACES IN THE JABODETABEK - Syakirotul Hayati; Jojok Dwiridhotjahjono (Universitas Muhammadiyah Semarang, 2026)
Analyzing the influence of social media marketing, online customer reviews, and online customer ratings on purchasing decisions is the objective of this research. This research is classified as associative quantitative research. A questionnaire was used as an instrument for data collection, using 165 samples through purposive sampling with the criteria of Dapoer Intan consumers in Greater Jakarta who had purchased products through the marketplace. Multiple linear regression analysis was used as the analysis technique to determine simultaneously and partially between independent and dependent variables. The results show that social media marketing, online reviews, and online ratings from consumers simultaneously have a significant positive influence on purchasing decisions. Social media marketing and online reviews from consumers partially have a significant positive influence on purchasing decisions, while online ratings have a non-significant positive influence on purchasing decisions. Keywords: purchasing decisions, social media marketing, online reviews, online ratings